Preparation method of zinc-nitrogen co-doped sponge-like porous carbon fiber material and application thereof
Patent Information
- Application Number
- CN202210259044.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-16
AI Technical Summary
[0004]针对现有技术的缺陷,本发明的目的在于提供一种锌氮共掺杂海绵状多孔碳纤维材料的制备方法及其应用,旨在解决现有三维集流体的密度和无效体积较大导致复合钾金属负极的质量和体积能量密度较低的问题
(1)本发明先制备锌基富氮三唑金属有机框架材料,再通过静电纺丝将金属有机框架颗粒串接在聚丙烯腈纤维上,然后通过高温退火处理得到超轻多孔的锌氮共掺杂碳纤维材料,该材料具有三维立体的互通网络结构,同时该材料中的锌和氮元素具有亲钾特性,可有效提升复合钾金属负极的能量密度。
Smart Images

Figure CN116804294B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of potassium-ion battery technology, and more specifically, relates to a method for preparing zinc-nitrogen co-doped sponge-like porous carbon fiber material and its application. Background Technology
[0002] With the rapid development of portable electronic devices, electrified transportation, and smart grids, the demand for rechargeable batteries, represented by lithium-ion batteries, is growing rapidly. However, with the further popularization of such energy storage technologies in the future, and given the limited reserves of lithium resources (approximately 0.002% abundance in the Earth's crust), lithium-ion batteries will face a lithium shortage. Therefore, energy storage technologies using elements more abundant in the Earth's crust as a medium are needed to address the lithium shortage. In contrast, potassium has reserves thousands of times greater than lithium (approximately 2.59% abundance in the Earth's crust), making potassium-ion batteries a promising alternative in large-scale energy storage, thus attracting widespread attention. Potassium metal anodes, due to their high energy density, have become the preferred choice for potassium batteries. However, the use of active potassium metal is accompanied by violent side reactions, which can lead to irreversible potassium consumption. During cycling, the drastic volume change of potassium can easily lead to unstable battery performance. Irregular potassium deposition can produce a large number of potassium dendrites. The continuous accumulation of dendrites will eventually pierce the separator, causing a short circuit in the battery, resulting in battery failure, or even safety accidents such as fire and explosion. This restricts the application of potassium metal anodes.
[0003] To address these issues, researchers have developed numerous strategies, such as controlling electrolyte composition or constructing artificial solid electrolyte interphase (SEI) membranes, using alloy potassium anodes, and employing composite potassium metal anodes supported by three-dimensional current collectors. The first two strategies have limited effectiveness in suppressing dendrite growth and potassium volume changes, while the use of three-dimensional current collectors has a relatively significant effect on improving the stability of potassium anodes. However, currently reported three-dimensional current collectors / substrates include porous metals and carbon cloth, which have large densities and ineffective volumes, significantly reducing the mass and volumetric energy density of composite anodes and limiting the practical application of this strategy. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing zinc-nitrogen co-doped sponge-like porous carbon fiber materials and their applications, thereby solving the problem that the large density and ineffective volume of existing three-dimensional current collectors result in low mass and volumetric energy density of composite potassium metal anodes.
[0005] To achieve the above objectives, the present invention provides a method for preparing zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: S1. Mix an alkaline solution containing zinc salt with 1,2,3-triazole and a surfactant, stir until homogeneous, wash and dry the precipitate generated by the reaction to obtain nano-sized metal-organic framework powder. S2. Disperse the metal-organic framework powder obtained in step S1 in N,N-dimethylformamide solution of polyacrylonitrile to obtain a spinning precursor solution, electrospin it, and dry it to obtain carbon fiber membrane precursor. S3. The carbon fiber membrane precursor obtained in step S2 is calcined to obtain zinc-nitrogen co-doped sponge-like porous carbon fiber material.
[0006] Preferably, in step S1, the molar ratio of the zinc salt to the 1,2,3-triazole is 1:(1~10), and the ratio of the amount of the 1,2,3-triazole to the amount of the surfactant is (1mL~5mL):(0.5g-4g).
[0007] Preferably, in step S1, the solvent in the alkaline solution includes N,N-dimethylformamide, ethanol, deionized water, and ammonia.
[0008] Preferably, in step S1, the ratio of zinc salt, N,N-dimethylformamide, ethanol, deionized water and ammonia in the alkaline solution containing zinc salt is (7mmol~30mmol):(10mL~40mL):(10mL~40mL):(15mL~60mL):(5mL~20mL).
[0009] Preferably, the zinc salt is one or more of zinc chloride, zinc acetate, zinc nitrate, and zinc sulfate.
[0010] Preferably, the surfactant is one or more selected from F-127, polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate.
[0011] Preferably, the surfactant is F-127.
[0012] Preferably, in step S1, the stirring reaction time is 0.5h to 5h.
[0013] Preferably, in step S2, the ratio of the metal-organic framework powder, polyacrylonitrile, and N,N-dimethylformamide is (0.3g~1g):(0.5g~1g):(3-10mL).
[0014] Preferably, in step S2, the electrospinning settings are as follows: voltage of 15kV~20kV, receiver rotation speed of 20rpm~50rpm, syringe needle size of 15~25, injection speed of 5μL / min~20μL / min, and spinning receiving distance of 5cm~25cm.
[0015] Preferably, in step S3, the calcination conditions are as follows: under an argon or nitrogen atmosphere, calcination is first carried out at 400℃~500℃ for 2h~6h, and then the temperature is raised to 600℃~900℃ for 1h~3h, with a heating rate of 2℃ / min~10℃ / min.
[0016] According to another aspect of the present invention, a zinc-nitrogen co-doped sponge-like porous carbon fiber material is provided, which is prepared by the above method.
[0017] According to another aspect of the present invention, a composite potassium metal anode is provided, comprising a zinc-nitrogen co-doped sponge-like porous carbon fiber material prepared by the above-described preparation method.
[0018] Preferably, the preparation method of the composite potassium metal anode includes: immersing the zinc-nitrogen co-doped sponge-like porous carbon fiber material into a molten potassium metal, wherein the molten potassium metal is adsorbed and composited into the zinc-nitrogen co-doped sponge-like porous carbon fiber material by capillary action to obtain the composite potassium metal anode.
[0019] According to another aspect of the present invention, a potassium-ion secondary battery is also provided, which includes the above-described composite potassium metal anode.
[0020] In summary, the technical solutions conceived by this invention have the following beneficial effects compared with the prior art: (1) In this invention, zinc-based nitrogen-rich triazole metal-organic framework material is first prepared, and then metal-organic framework particles are strung together on polyacrylonitrile fiber by electrospinning. Then, ultralight porous zinc-nitrogen co-doped carbon fiber material is obtained by high-temperature annealing. The material has a three-dimensional interconnected network structure. At the same time, the zinc and nitrogen elements in the material have potassium affinity, which can effectively improve the energy density of composite potassium metal anode.
[0021] (2) By controlling the amount of each additive used in the preparation process, this invention can achieve controllable doping of zinc and nitrogen elements and regulate the pore structure of porous carbon fiber materials, achieving a specific surface area of 85 m². 2 g -1 The above has a surface mass of only 0.5 mg / cm³. -2 about.
[0022] (3) The zinc-nitrogen co-doped sponge-like porous carbon fiber material prepared by the present invention has special zinc-nitrogen potassium-loving sites, which can significantly reduce the nucleation overpotential (15 mV) when used as a current collector.
[0023] (4) Since the porous carbon fiber material provided by the present invention has a well-developed multi-level channel structure, it can rapidly adsorb molten potassium metal by means of capillary action, thereby realizing the rapid preparation of composite potassium metal anode.
[0024] (5) The composite potassium metal anode prepared by melt adsorption in this invention has an extremely high metal loading (97wt%) and inhibits the growth of potassium dendrites during electrochemical processes. Its discharge specific capacity can reach 667 mA hg. -1 It can cycle stably for more than 1000 hours. Attached Figure Description
[0025] Figure 1 The image shows the XRD pattern of the metal-organic framework nMET-6 powder and the nMET-6 / PAN spinning prepared in Example 1 of this invention.
[0026] Figure 2 This is a SEM image of the metal-organic framework nMET-6 powder prepared in Example 1 of the present invention.
[0027] Figure 3 The image shows the XRD pattern of the porous carbon fiber material MCNF prepared in Example 1 of this invention.
[0028] Figure 4 The images are SEM images of the porous carbon fiber material MCNF prepared in Example 1 of this invention at different magnifications.
[0029] Figure 5 The images show TEM images (a) and elemental distribution diagrams (b) of the porous carbon fiber material MCNF prepared in Example 1 of this invention.
[0030] Figure 6 This is a SEM image of the metal-organic framework nMET-6 powder prepared in Example 2 of the present invention.
[0031] Figure 7 This is a SEM image of the metal-organic framework nMET-6 powder prepared in Example 3 of the present invention.
[0032] Figure 8 This is a SEM image of the metal-organic framework MET-6 powder prepared in Comparative Example 1 of the present invention.
[0033] Figure 9 The images show (a) and (b) of the carbon fiber material cPAN-Zn prepared in Comparative Example 3 of this invention.
[0034] Figure 10 This is a graph showing the potassium deposition voltage curve of the first discharge cycle of MCNF and copper foil in Embodiment 6 of the present invention.
[0035] Figure 11 This is a diagram showing the coulombic efficiency of potassium deposition stripping cycle for MCNF and copper foil in Example 6 of the present invention.
[0036] Figure 12This is a discharge capacity-voltage curve of the K-MCNF||Cu battery in Example 7 of the present invention.
[0037] Figure 13 This is a rate test time-voltage curve of the symmetrical cells K-MCNF||K-MCNF and K-Cu||K-Cu in Embodiment 7 of the present invention.
[0038] Figure 14 This is a constant current long cycle time-voltage curve of the symmetrical cells K-MCNF||K-MCNF and K-Cu||K-Cu in Embodiment 7 of the present invention.
[0039] Figure 15 This is the energy spectrum of the MCNF electrode after etching in Example 8 of the present invention.
[0040] Figure 16 This is a graph showing the potassium deposition voltage curves of the MCNF electrode and the etched MCNF electrode in Embodiment 8 of the present invention.
[0041] Figure 17 In Embodiment 9 of the present invention, K-MCNF||Se 0.05 S 0.95 @pPAN and K-Cu||Se 0.05 S 0.95 @pPAN Rate performance graph of full battery.
[0042] Figure 18 In Embodiment 9 of the present invention, K-MCNF||Se 0.05 S 0.95 @pPAN and K-Cu||Se 0.05 S 0.95 @pPAN full cell long-cycle performance graph. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0044] The present invention provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: S1. Mix the alkaline solution containing zinc salt with 1,2,3-triazole and stir until homogeneous. Wash and dry the precipitate generated by the reaction to obtain nano-sized metal-organic framework powder. S2. Disperse the metal-organic framework powder obtained in step S1 in N,N-dimethylformamide solution of polyacrylonitrile to obtain a spinning precursor solution, electrospin it, and dry it to obtain carbon fiber membrane precursor. S3. The carbon fiber membrane precursor obtained in step S2 is calcined to obtain zinc-nitrogen co-doped sponge-like porous carbon fiber material.
[0045] Zn(II) is d 10 Metal ions exhibit flexible coordination modes, often displaying tetrahedral coordination. Triazoles are organic ligands with strong coordination orientation and bonding capabilities, readily deprotonating to become excellent linkers. Zinc ions and 1,2,3-triazoles self-assemble through coordination bonds to form metal-organic frameworks (MOFs) with intramolecular pores. Using triazole-rich nanostructured MOFs as pore-forming templates, they are uniformly mixed with polyacrylonitrile and electrospun, followed by annealing to obtain nitrogen-doped porous carbon fiber materials retaining zinc clusters. The significant volume change of triazoles at high temperatures results in a well-developed hierarchical pore structure and a large specific surface area in the prepared material. The zinc and nitrogen elements in the zinc-nitrogen co-doped sponge-like porous carbon fiber material of this invention have potassium affinity properties. As a current collector, they can significantly reduce the nucleation overpotential. Its special sponge-like interconnected hollow structure can realize the rapid adsorption of molten potassium metal, increase the metal loading in the composite negative electrode, and inhibit dendrite growth in the electrochemical process, thereby improving the battery cycle life.
[0046] In step S1 of some embodiments, the zinc salt can be any soluble zinc salt, including but not limited to zinc chloride, zinc acetate, zinc nitrate, zinc sulfate, etc. The solvent in the alkaline solution includes N,N-dimethylformamide (DMF), ethanol, deionized water, and ammonia. This solvent can effectively dissolve 1,2,3-triazole. Furthermore, since it is difficult for 1,2,3-triazole to deprotonate before coordination at room temperature, this invention utilizes ammonia to regulate the solution environment to a slightly alkaline state, which is more conducive to the reaction. Adding a surfactant can make the resulting metal-organic framework particles smaller, which is more conducive to their attachment to polyacrylonitrile fibers during spinning and to the in-situ formation of appropriately sized porous structures on the fibers. The surfactant can be F-127, polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), etc., with F-127 being more preferred.
[0047] In some embodiments, the molar ratio of the zinc salt to the 1,2,3-triazole is 1:(1~10), preferably 1:(1~5), and more preferably 1:3. In the alkaline solution containing the zinc salt, the ratio of zinc salt, N,N-dimethylformamide, ethanol, deionized water, and ammonia is (7mmol~30mmol):(10mL~40mL):(10mL~40mL):(15mL~60mL):(5mL~20mL). The ratio of 1,2,3-triazole to surfactant is (1mL~5mL):(0.5g~4g).
[0048] In a preferred embodiment, in step S1, the zinc salt is first dissolved in an alkaline solvent to obtain a first solution, and 1,2,3-triazole is mixed with a surfactant to obtain a second solution. The first solution is then added to the second solution for stirring and reaction. This allows the reactants to dissolve completely on their own, preventing uneven reaction due to excessively high local concentrations. When the zinc salt and 1,2,3-triazole are mixed, the triazole can slowly deprotonate, slowing down the reaction rate and making the reaction more complete.
[0049] In step S1 of this embodiment, the coordination reaction between zinc salt and 1,2,3-triazole is carried out under mild conditions, without the need for high temperature and high pressure, and can be carried out within a temperature range of 5℃ to 50℃. To ensure a more complete reaction, the stirring time should preferably be 0.5h to 5h. As a preferred embodiment, the precipitate generated by the reaction is washed and filtered multiple times with N,N-dimethylformamide, ethanol, and deionized water, respectively, and then the washed precipitate is dried at a temperature of 80℃ to 120℃ for at least 12h.
[0050] In step S2 of some embodiments, the ratio of the metal-organic framework powder, polyacrylonitrile, and N,N-dimethylformamide is (0.3g~1g):(0.5g~1g):(3-10mL).
[0051] In some embodiments, the electrospinning process is carried out in an environment with a temperature of 5°C to 50°C and a humidity of 10%RH to 50%RH, and the parameters are set as follows: voltage of 15kV to 20kV, receiver rotation speed of 20rpm to 50rpm, syringe needle size of 15 to 25, injection speed of 5μL / min to 20μL / min, and spinning receiving distance of 5cm to 25cm.
[0052] In step S3 of some embodiments, the calcination conditions are as follows: calcination at 400℃~500℃ for 2h~6h under an argon or nitrogen atmosphere, followed by calcination at 600℃~900℃ for 1h~3h, with a heating rate of 2℃ / min~10℃ / min. Through this two-step calcination process, the calcination temperature and holding time are reasonably controlled, ensuring complete carbonization of the precursor and uniform fusion of the metal-organic framework particles and carbon fibers.
[0053] The present invention provides a composite potassium metal anode, comprising a zinc-nitrogen co-doped sponge-like porous carbon fiber material prepared by the above method. Combining this ultralight carbon fiber material with a well-developed pore structure with potassium metal can yield a composite anode with high energy density.
[0054] In some embodiments, the preparation method of the composite potassium metal anode is as follows: heating bulk potassium metal to a molten state and having a certain fluidity, immersing zinc-nitrogen co-doped sponge-like porous carbon fiber material into the molten potassium metal, and the molten potassium metal adsorbing and combining with the zinc-nitrogen co-doped sponge-like porous carbon fiber material by capillary action to obtain the composite potassium metal anode.
[0055] On the other hand, the present invention also provides a potassium-ion secondary battery comprising the aforementioned composite potassium metal negative electrode. More preferably, the positive electrode of the battery is Se. 0.05 S 0.95 The @pPAN composite sulfur cathode uses KFSI-EC / DEC as the electrolyte and glass fiber as the separator.
[0056] The above technical solution will be described in detail below with reference to specific embodiments.
[0057] Example 1 This embodiment provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL N,N-dimethylformamide (DMF), 20 mL ethanol, 30 mL deionized water, and 10 mL ammonia to form a first solution. 2.5 mL of 1,2,3-triazole was mixed with 1.2 g of surfactant F-127 to obtain a second solution. The first solution was added to the second solution, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated nMET-6. Its X-ray diffraction (XRD) pattern and scanning electron microscope (SEM) image are shown below. Figure 1 and Figure 2 As shown.
[0058] 0.6 g of nMET-6 was dispersed in 5 mL of DMF, and 0.5 g of polyacrylonitrile (PAN) was added and stirred to dissolve, yielding dispersion D1. D1 was then electrospun at a feed rate of 12 μL / min. -1 The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 600 ℃ for 1 hour, with a heating rate of 5 ℃ / min. -1 The resulting calcined sample is designated MCNF. Its X-ray diffraction pattern and scanning electron microscope image are shown below. Figure 3 and Figure 4 As shown, the transmission electron microscope (TEM) image and elemental distribution are as follows: Figure 5 As shown in the XRD pattern, the obtained sample is amorphous, indicating that there are no obvious crystalline products inside. Figure 4 It can be seen that the fiber surface has pores with a diameter of about 50 nm evenly distributed, the fiber diameter is about 500 nm, and the inside of the fiber is a connected cavity. Figure 5 The elemental distribution diagram shows that nitrogen and zinc are uniformly distributed in MCNF, indicating that zinc exists in nanoscale clusters.
[0059] Approximately 50 mg of MCNF was subjected to dynamic vacuum treatment at 150 °C for 6 hours, and the porosity of the MCNF was analyzed using a specific surface area analyzer. The results are shown in Table 1. The obtained MCNF has a high specific surface area of 90.6 m². 2 g -1 Its pore volume is 0.227 cc g -1 The MCNF exhibits a wide pore size distribution, including micropores of 1.2 nm and mesopores larger than 4 nm, demonstrating stepwise pore characteristics. Its areal mass is extremely low, at 0.5 mg cm⁻¹. -2 Compared to other commercially available three-dimensional current collectors such as nickel foam, carbon cloth, and carbon paper, MCNF has an order-of-magnitude increase in specific surface area and is 10-100 times lighter, indicating its significant advantages as a three-dimensional current collector.
[0060] Example 2 This embodiment provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL N,N-dimethylformamide (DMF), 20 mL ethanol, 30 mL deionized water, and 10 mL ammonia to form a first solution. 6 mL of 1,2,3-triazole was mixed with 1.2 g of surfactant F-127 to obtain a second solution. The first solution was added to the second solution, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated nMET-6, and its SEM image is shown below. Figure 6 As shown.
[0061] 0.6 g of nMET-6 was dispersed in 5 mL of DMF, and 0.5 g of polyacrylonitrile (PAN) was added and stirred to dissolve, yielding a dispersion. The dispersion was then subjected to electrospinning at a feed rate of 12 μL / min. -1 The needles were size 20, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 600 ℃ for 1 hour, with a heating rate of 5 ℃ / min. -1 The resulting calcined sample is a porous carbon fiber material.
[0062] Example 3 This embodiment provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL N,N-dimethylformamide (DMF), 20 mL ethanol, 30 mL deionized water, and 10 mL ammonia to form a first solution. 0.8 mL of 1,2,3-triazole was mixed with 2 g of surfactant F-127 to obtain a second solution. The first solution was added to the second solution, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated nMET-6, and its SEM image is shown below. Figure 7 As shown.
[0063] 0.6 g of nMET-6 was dispersed in 5 mL of DMF, and 0.5 g of polyacrylonitrile (PAN) was added and stirred to dissolve, yielding a dispersion. The dispersion was then subjected to electrospinning at a feed rate of 12 μL / min. -1The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 600 ℃ for 1 hour, with a heating rate of 5 ℃ / min. -1 The resulting calcined sample is a porous carbon fiber material.
[0064] Example 4 This embodiment provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL of N,N-dimethylformamide (DMF), 20 mL of ethanol, 30 mL of deionized water, and 10 mL of ammonia to form a first solution. 2.5 mL of 1,2,3-triazole was mixed with 1.2 g of surfactant F-127 to obtain a second solution. The first solution was added to the second solution, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated nMET-6.
[0065] 0.6 g of nMET-6 was dispersed in 5 mL of DMF, and 0.5 g of polyacrylonitrile (PAN) was added and stirred to dissolve, yielding a dispersion. The dispersion was then subjected to electrospinning at a feed rate of 12 μL / min. -1 The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun yarn sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 700 ℃ for 1 hour, with a heating rate of 10 ℃ / min. -1 The resulting calcined sample is a porous carbon fiber material.
[0066] Example 5 This embodiment provides a method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, comprising the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL of N,N-dimethylformamide (DMF), 20 mL of ethanol, 30 mL of deionized water, and 10 mL of ammonia to form a first solution. 2.5 mL of 1,2,3-triazole was mixed with 1.2 g of surfactant F-127 to obtain a second solution. The first solution was added to the second solution, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated nMET-6.
[0067] 0.6 g of nMET-6 was dispersed in 5 mL of DMF, and 0.5 g of polyacrylonitrile (PAN) was added and stirred to dissolve, yielding dispersion D1. D1 was then electrospun at a feed rate of 12 μL / min. -1 The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun yarn sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 900 ℃ for 1 hour, with a heating rate of 3 ℃ / min. -1 The resulting calcined sample is a porous carbon fiber material.
[0068] Comparative Example 1 This comparative example provides a MOF material, the preparation method of which includes the following steps: 2 g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20 mL N,N-dimethylformamide (DMF), 20 mL ethanol, 30 mL deionized water, and 10 mL ammonia to form a first solution. This first solution was added to 4 mL of 1,2,3-triazole, and the mixture was stirred continuously at room temperature for 2 hours. The resulting white precipitate was washed once with DMF and once with ethanol, and then dried at 100 °C for 24 hours. The resulting white powder was designated MET-6, and its SEM image is shown below. Figure 8 As shown in the figure, without the participation of F-127, the resulting MOF material particles are too large to meet the requirements for spinning nanofibers.
[0069] Comparative Example 2 This comparative example provides a nitrogen-containing carbon fiber material, the preparation method of which includes the following steps: 0.5 g of PAN was dissolved in 5 mL of DMF and stirred at room temperature for 12 hours to obtain solution R1. R1 was then electrospun at a feed rate of 12 μL / min. -1 The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 600 ℃ for 1 hour, with a heating rate of 5 ℃ / min. -1 The resulting calcined sample is denoted as cPAN.
[0070] Approximately 50 mg of cPAN was subjected to dynamic vacuum treatment at 150 °C for 6 hours, and the porosity of the cPAN was analyzed using a specific surface area analyzer. The results are shown in Table 1. The specific surface area of the obtained cPAN was only 30.0 m². 2 g -1 0.044 cc g-1 The main pore size is approximately 3.1 nm, with no obvious hierarchical pore distribution. This indicates that PAN cannot generate a rich porous structure at high temperatures, and also proves that nMET-6 has a pore-forming effect after decomposition.
[0071] Comparative Example 3 This comparative example provides a zinc-nitrogen co-doped carbon fiber material, the preparation method of which includes the following steps: 0.6 g of Zn(CH3COO)2 was dissolved in 5 mL of DMF and sonicated for 30 min. Then, 0.5 g of PAN was dissolved in the solution, and the mixture was stirred at room temperature for 12 hours to obtain solution R2. R2 was then electrospun at a feed rate of 12 μL / min. -1 The needles were size 19, the distance between the needle and the plate was 15 cm, the ambient humidity was 30%RH, and the temperature was 25 ℃. The resulting spun sample was dried at 80 ℃ for 12 hours, and then calcined in an argon-filled tube furnace under the following conditions: 500 ℃ for 2 hours, 600 ℃ for 1 hour, with a heating rate of 5 ℃ / min. -1 The resulting calcined sample is denoted as cPAN-Zn.
[0072] Approximately 50 mg of cPAN-Zn was subjected to dynamic vacuum treatment at 150 °C for 6 hours, and the porosity of cPAN-Zn was analyzed using a specific surface area analyzer. The results are shown in Table 1, indicating that the specific surface area of the obtained cPAN-Zn was only 27.2 m². 2 g -1 The pore volume is 0.050 cc g -1 Its pore size distribution is the same as that of cPAN. Meanwhile, the morphology of cPAN-Zn is as follows: Figure 9 As can be seen, large zinc particles are distributed on its surface and inside. This indicates that nMET-6, as a zinc source, has the effect of inhibiting zinc particle agglomeration at high temperatures and improving the reactivity of elemental zinc. In contrast, ordinary zinc salts tend to agglomerate at high temperatures, forming larger particles.
[0073] Table 1. Pore properties and surface quality of MCNF and different comparative samples in the embodiments of the present invention.
[0074] Example 6 In this embodiment, zinc-nitrogen co-doped sponge-like porous carbon fiber material (prepared in Example 1) with a larger specific surface area was used as the electrode for testing. MCNF slices obtained in Example 1 were cut into 10 mm diameter circular pieces as electrode A1, and copper foil slices were used as the control electrode B1. A battery was assembled and charge-discharge efficiency cycle test was performed. A potassium metal sheet was used as the negative electrode, and a 1 mol / L electrolyte was used. -1Potassium bis(fluorosulfonyl)imide (KFSI) was dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1). Glass fiber was used as the separator, and CR2032 stainless steel was used for the battery casing. The resulting batteries were denoted as K||MCNF and K||Cu, respectively. The reaction was carried out at 0.5 mA cm⁻¹. -2 Discharge for 1 hour, then charge to 1 V with the same current, and repeat this process cyclically. The ratio of the charging cutoff capacity to the discharging capacity is recorded as the coulombic efficiency.
[0075] Figure 10 The voltage curves of the battery during the first discharge deposition process show that MCNF has a significantly reduced nucleation overpotential of only 15 mV, while the nucleation overpotential of copper foil is as high as 43 mV, demonstrating the outstanding potassium affinity of MCNF. Figure 11 Reflecting the corresponding cyclic coulombic efficiency, it can be seen that K||MCNF can cycle for more than 200 times with an average coulombic efficiency of 97%, which is more than 4 times that of copper foil, demonstrating superior cyclic stability.
[0076] Example 7 This embodiment prepares a composite potassium metal anode. The specific method is as follows: The MCNF obtained in Example 1 is cut into 5cm×5cm pieces, and the edges are immersed in molten potassium metal at 150℃ to adsorb and recombine potassium, thus preparing the composite potassium metal anode K-MCNF. The obtained K-MCNF is sliced into 10 mm diameter circular pieces as electrode A2.
[0077] In this embodiment, A2 is used as the negative electrode of a potassium-ion battery, and a coin cell is assembled with a stainless steel positive electrode. The electrolyte used is 1 mol / L. -1 KFSI was dissolved in a mixed solution of EC and DEC (volume ratio 1:1), and glass fiber was used as the separator. The resulting battery was subjected to constant current discharge at a current of 0.05 mA cm⁻¹. -2 The cutoff voltage is -3V. Figure 12 The discharge capacity of the A2 electrode is 667 mAh g. -1 The active loading is as high as 97% of the theoretical capacity of potassium metal, indicating that the obtained MCNF current collector has an extremely high active loading.
[0078] A symmetrical K-MCNF||K-MCNF cells were assembled using A2 as the electrode, with a 1 mol L electrolyte. -1 KFSI was dissolved in a mixed solution of EC and DEC (volume ratio 1:1), and glass fiber was used as the separator. As a control, a symmetrical cell was assembled using a potassium foil-supported plate B2 to obtain K-Cu||K-Cu. The resulting cells were subjected to rate performance testing. Figure 13 As shown, at 0.5, 1, 2, 3, and 5 mA cm⁻¹ -2At a current density of 1 mA cm⁻¹, both K-MCNF||K-MCNF exhibited smaller overpotentials, indicating that the A2 electrode possesses better reaction kinetics. Symmetrical cells K-MCNF||K-MCNF and K-Cu||K-Cu were subjected to a constant current of 1 mA cm⁻¹. -2 Constant capacity 1 mAh cm -2 Next loop, Figure 14 It can be seen that the lifespan of electrode A2 is 24 times longer than that of electrode B2.
[0079] Example 8 The MCNF prepared in Example 1 was cut into 10 mm diameter round slices, and a diluted hydrochloric acid solution (3 mol L) was added. -1 Slowly add and wet the MCNF, let it stand at room temperature for 2 hours, then slowly rinse the MCNF with deionized water until the pH of the washing solution becomes 7. Dry the resulting etched MCNF at 100°C for 12 hours, and record it as electrode A3. Figure 15 The energy spectrum of A3 shows that the material no longer contains zinc after etching.
[0080] Using A3 as the positive electrode and potassium metal sheet as the negative electrode, the electrolyte is 1 mol L / L. -1 KFSI was dissolved in a mixed solution of EC and DEC (volume ratio 1:1), and a coin cell was assembled using glass fiber as the separator. The assembled cell was powered by a 0.5 mA cm⁻¹. -2 Discharge for 1 hour and record the discharge voltage curve. Figure 16 It can be seen that the nucleation overpotential of A3 is 30mV, which is significantly higher than that of MCNF (15mV), indicating that the presence of zinc is beneficial to improving the potassium affinity of the electrode.
[0081] Example 9 In this embodiment, electrodes A2 and B2 are used as negative electrodes, and Se... 0.05 S 0.95 @pPAN composite sulfur cathode assembly of potassium-sulfur full cell, using 1 mol L electrolyte -1 KFSI was dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1), with glass fiber as the diaphragm.
[0082] The obtained battery was subjected to rate performance testing, such as... Figure 17 As shown, at concentrations of 0.1, 0.2, 0.5, 1, 2, and 3 A g... -1 At current densities of 0.2 mA g, the A2 cells consistently exhibited higher specific capacity, with the capacity decreasing when the current returned to 0.2 mA g. -1 Afterwards, its specific capacity can still recover to 800mAh g. -1 The capacity of cell B2 decreased sharply under the same conditions as the initial value. This result indicates that the full cell using electrode A2 has better rate performance and stability.
[0083] The resulting battery was subjected to a constant current long-cycle test, such as... Figure 18 As shown, at 0.5A g -1 Under the given current, the A2 battery retains 60% of its capacity after 600 cycles, while the B2 battery retains 60% of its initial capacity after only 100 cycles. This demonstrates the excellent cycle stability of the A2 electrode and its practical application as a negative electrode in potassium batteries.
[0084] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a zinc-nitrogen co-doped sponge-like porous carbon fiber material, characterized in that, Includes the following steps: S1. An alkaline solution containing zinc salt is mixed with 1,2,3-triazole and a surfactant, and stirred until homogeneous. The precipitate generated by the reaction is washed and dried to obtain nano-sized metal-organic framework powder. The solvent in the alkaline solution includes N,N-dimethylformamide, ethanol, deionized water and ammonia. The surfactant is one or more of F-127, polyvinylpyrrolidone, hexadecyltrimethylammonium bromide and sodium dodecyl sulfate. The molar ratio of zinc salt to 1,2,3-triazole is 1:(1~10). The ratio of the amount of 1,2,3-triazole to the amount of surfactant is (1mL~5mL):(0.5g-4g). S2. The metal-organic framework powder obtained in step S1 is dispersed in an N,N-dimethylformamide solution of polyacrylonitrile to obtain a spinning precursor solution. The solution is then electrospun and dried to obtain a carbon fiber membrane precursor. The ratio of the metal-organic framework powder, polyacrylonitrile, and N,N-dimethylformamide is (0.3g~1g):(0.5g~1g):(3-10mL). S3. The carbon fiber membrane precursor obtained in step S2 is calcined to obtain zinc-nitrogen co-doped sponge-like porous carbon fiber material. The calcination conditions are as follows: calcined at 400℃~500℃ for 2h~6h in an argon or nitrogen atmosphere, and then heated to 600℃~900℃ for 1h~3h, with a heating rate of 2℃ / min~10℃ / min.
2. The preparation method according to claim 1, characterized in that: In step S1, the stirring reaction time is 0.5h to 5h.
3. The preparation method according to claim 1, characterized in that, In step S2, the electrospinning settings are as follows: voltage is 15kV~20kV, receiver rotation speed is 20rpm~50rpm, syringe needle size is 15~25, injection speed is 5μL / min~20μL / min, and spinning receiving distance is 5cm~25cm.
4. A composite potassium metal anode, characterized in that: This includes zinc-nitrogen co-doped sponge-like porous carbon fiber materials prepared using any one of the preparation methods described in claims 1-3.
5. The composite potassium metal anode according to claim 4, characterized in that, The method for preparing the composite potassium metal anode includes: immersing the zinc-nitrogen co-doped sponge-like porous carbon fiber material into a molten potassium metal, wherein the molten potassium metal is adsorbed and composited into the zinc-nitrogen co-doped sponge-like porous carbon fiber material by capillary action, thereby obtaining the composite potassium metal anode.
6. A potassium-ion secondary battery, characterized in that: Including the composite potassium metal anode as described in claim 4 or 5.
Citation Information
Patent Citations
Nitrogen-doped multi-porous carbon negative electrode material and preparation method and application thereof
CN105609771A
Preparation method of carbon nanofiber electrode material based on MOFs derived metal oxide
CN111081995A
Lithium ion battery negative electrode material, lithium ion battery and preparation method
CN115172683A